Odpowiedź :
[tex] \sqrt{(x_2 - x_1 {)}^{2} + ( y_2 - y_1 {)}^{2} } [/tex]
[tex] \sqrt{(2 - ( - 3) {)}^{2} + ( - 5 - 4 {)}^{2} } = \\ = \sqrt{(2 + 3 {)}^{2} + ( - 9 {)}^{2} } = \\ = \sqrt{ {5}^{2} + 81 } = \\ = \sqrt{25 + 81} = \\ = \sqrt{106} \\ [/tex]
Witaj :)
Wzór na długość odcinka o punktach A i B
[tex]A=(x,y) \ oraz \ B=(x,y)\\\\|AB|=\sqrt{(x_B-x_A)^2+(y_B-y_A)^2}[/tex]
Obliczenia
[tex]A=(-3,4)\Longrightarrow x_A=-3, \ y_A=4\\\\B=(2,-5)\Longrightarrow x_B=2, \ y_B=-5\\\\|AB|=\sqrt{(2-(-3))^2+(-5-4)^2}\\\\|AB|=\sqrt{(2+3)^2+(-9)^2}\\\\|AB|=\sqrt{5^2+81}=\sqrt{25+81}\\\\\huge\boxed{|AB|=\sqrt{106}}[/tex]